LEKSIKON JAWA SEBAGAI CERMINAN BUDAYA DALAM NOVEL PEREMPUAN BERKALUNG SORBAN KARYA ABIDAH ELKHALIEQY: KAJIAN STILISTIKA - Ahmad Faizi (LITERASI: Indonesian Journal of Humanities, 2015)
This study aims to reveal the representation of the boarding school women in PBS novel. Sources of data in this study are linguistic data contained in the novel entitled Perempuan Berkalung Sorban by Abidah El-Kholieqy. The data were collected by the method of see and note and then were analyzed by using stylistics theories. The results of this study indicate that the use of Javanese lexicons in the PBS reflects the cultural values that exist in society and the boarding school families. Various utilizations of Javanese lexicons are intentionally made to give birth to the aesthetic values on PBS. Aesthetic values appear with the precision of meaning in the choice of words used by Abidah.Keywords: culture, lexicon, boarding, stylistics